Rapport Building in community settings - Kumar, Santosh; Negi, Sapna (Indian Journal of Community Health, 2023)
Establishing good rapport and interpersonal relationship is crucial aspect for public health researcher to embark upon authentic information and concerns of local community that later might have a bigger public health impact in policy making. Despite of its importance, researchers often fail to favourably present themselves in front of participants. The active listening, maintaining eye contact, self disclosure, tuning in, sharing expectations and intentions, non verbal cues, persistent contact and being empathetic are some of the most common techniques of rapport building discussed in literatures. Despite the fact that they have been proved to be beneficial, they do not provide clarity on “what, when, or where”. As a result, this article suggests a step-by-step approach that a researcher might use when conducting community-based research.